Nanoscale asphalt regeneration modified material and preparation method thereof

Through the use of nano-scale asphalt regeneration modified materials, the "colloid" structure that breaks down the polar groups of asphalt has solved the problems of poor anti-aging performance and poor diffusion permeability of existing asphalt regenerators, and effectively repair and performance recovery of asphalt pavement.

CN119613975APending Publication Date: 2025-03-14JIANGSU MODERN ROAD & BRIDGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411608629.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing asphalt regenerator has uneven quality, poor anti-aging performance, and poor diffusion and permeability between aging asphalt, making it difficult to effectively repair the aged asphalt pavement.

Method used

Using nano-scale asphalt regeneration modified materials, the combination of composite nano-modified materials, nano-scale fully vulcanized powder modified rubber, super tackifying resin, nano-adjuvant and surfactant materials can break up the "gum particles" structure of asphalt polar groups, reduce the friction resistance of asphalt molecules, soften the asphalt, and thus restore its performance.

Benefits of technology

It effectively solves the problems of poor compatibility with old asphalt and regenerating agents and poor diffusion and permeability between aged asphalt, significantly improves the component imbalance of asphalt materials, restores the design and use performance of the mixture, and achieves the effect of repairing aged asphalt pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613975A_ABST
    Figure CN119613975A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-scale asphalt regeneration modified material which is prepared from the following components in parts by weight: 15-40 parts of a composite nano-modified material, 15-40 parts of nano-scale fully-vulcanized powder modified rubber, 3-10 parts of super tackifying resin, 5-15 parts of a nano auxiliary agent and 20-40 parts of a surface active material. The preparation method comprises the following steps: preparing raw materials, performing catalytic reaction, premixing, extruding and granulating, and grinding. According to the invention, a colloidal particle structure formed by polar groups of asphalt can be scattered or separated through a strong charge attraction effect between the polar groups subjected to'breaking 'oxidation, so that the friction resistance of asphalt molecules is reduced, the viscosity is reduced, the asphalt is softened, and the performance of the asphalt is recovered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road asphalt regeneration materials, and in particular to a nano-scale asphalt regeneration modified material and a preparation method thereof. Background Art

[0002] The construction of asphalt pavement consumes a lot of natural resources, but natural resources are limited. With the scarcity and even depletion of oil resources, the output of high-quality asphalt materials will be seriously affected. As for stone materials, due to current environmental protection requirements and policies, high-quality stone materials available for asphalt pavement are becoming increasingly scarce, and the sources of stone materials are becoming fewer and fewer, which increases the transportation distance of stone materials and the cost. In short, the scarcity of natural resources has gradually affected the further development of road traffic.

[0004] The so-called asphalt regeneration is the process of restoring the performance of aged asphalt through some chemical and physical means. In practical applications, this function is mainly achieved by adding regeneration agents. At present, foreign-produced regeneration agents have entered my country's engineering market in large quantities, such as the RF series regeneration agents developed by Japan's JSR Corporation, the AE series regeneration agents and the Golden Bear Oil series regeneration agents of the United States.

[0005] Although there are various brands of regeneration agent products on the market, the quality of these regeneration agents varies greatly and the effects of their use still vary greatly. However, in general, there are two main types of regeneration agents:

[0006] ① Synthesis of waste oil and extracted oil: The raw materials of this type of regeneration agent are mainly waste light oil, such as diesel, engine oil, lubricating oil, extracted oil, etc. The main effect of this type of regeneration agent is that it can achieve better workability and reduce the viscosity of the material. However, this type of regeneration agent is more volatile and easily decomposed under light and high temperature conditions, and its durability is slightly poor.

[0007] ② Resin-oil synthesis: This type of product is mainly a mixture of resin and low-viscosity oil. The addition of resin can enhance the durability of the regeneration agent, and through the viscosity increase and copolymerization of light oil, it can effectively solve the problem of poor compatibility between old asphalt and regeneration agent. This type of regeneration agent has a good effect, but due to the requirements of the materials used and the production process, the cost is relatively high.

[0008] Therefore, a nano-scale asphalt regeneration and modification material is invented. The quality of the regeneration agents on the market is uneven, and most of them have shortcomings such as poor anti-aging performance and poor diffusion and permeability with aged asphalt. Nanomaterials are used to solve the problems of poor compatibility between old asphalt and regeneration agents, and poor diffusion and permeability with aged asphalt. The material can effectively regulate and improve the component imbalance caused by aging of asphalt materials, restore the designed performance of the mixture, and thus achieve the purpose of repairing aged asphalt pavement. Summary of the invention

[0009] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0010] In view of the problems existing in the above-mentioned existing nano-scale asphalt regeneration and modification materials and preparation methods thereof, the present invention is proposed.

[0011] Therefore, the purpose of the present invention is to provide a nano-scale asphalt regeneration and modification material and a preparation method thereof, which enables the "colloid particle" structure formed by the polar groups of asphalt to be broken up or separated, thereby reducing the friction resistance of asphalt molecules, reducing viscosity, softening asphalt, and further restoring asphalt performance.

[0012] In order to solve the above technical problems, the present invention provides the following technical solutions: a nano-scale asphalt regeneration modified material, prepared from the following components, by weight: 15-40 parts of composite nano-modified materials, 15-40 parts of nano-scale fully vulcanized powder modified rubber, 3-10 parts of super tackifying resin, 5-15 parts of nano-additives, 20-40 parts of surfactants, and prepared through factory prefabrication, catalytic reaction, premixing, extrusion granulation, and grinding processes.

[0013] As a preferred embodiment of the nano-scale asphalt regeneration modification material of the present invention, the composite nano-modified material is composed of nano-scale titanium dioxide or its modified polymer, UHMWPE (ultra-high molecular weight polyethylene) and calcium sulfate whiskers.

[0014] As a preferred embodiment of the nano-scale asphalt regeneration and modification material of the present invention, the super tackifying resin is KORESIN super tackifying resin or GXH138 super tackifying resin.

[0015] As a preferred embodiment of the nano-scale asphalt regeneration modification material of the present invention, the nano-scale rubber modification material is ultra-fine fully vulcanized powder rubber modified styrene-butadiene rubber.

[0016] As a preferred solution of the nano-scale asphalt regeneration and modification material of the present invention, the nano-additive is a special modified polyether siloxane copolymer.

[0017] As a preferred embodiment of the nano-scale asphalt regeneration and modification material of the present invention, the surfactant material is fatty acid esters, including fatty acid glycerides and sorbitol fatty acid esters.

[0018] A method for preparing a nano-scale asphalt regeneration modified material specifically comprises the following steps:

[0019] Step 1: Composite nano-modified material: using butyl titanate as raw material, hydrolyzing, polycondensing, and then polycondensing to obtain gel, and drying the gel to prepare nano titanium dioxide; ultra-high molecular weight polyethylene is prepared by pressing, sintering, and pressing methods, and the process flow is as follows: prepare the raw materials in proportion; dry at 100°C and stir at high speed until the materials are evenly dispersed; press at 50Mpa, heat up to 170°C for sintering; press and shape again at 30Mpa, then cool to 70°C for demolding, grinding, and mechanical processing to prepare; through calcium salt and sulfate solution, mechanical stirring, mixing, and then light stirring, aging for 24 hours to obtain calcium sulfate whiskers, and the three nano materials are prepared by compounding and blending in a ratio of 1:1:1;

[0020] Step 2: Super tackifying resin: synthesized from the condensation product of butylphenol and acetylene or prepared from rosin and petroleum resin as basic raw materials through processes such as decolorization, esterification, grafting, and stabilization;

[0021] Step 3: Nano-scale fully vulcanized powder modified rubber: using styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber, and chloroprene rubber as raw materials, cross-linking the latex through electron rays, and then spray drying to prepare it;

[0022] Step 4: The nano-additive is prepared from high-hydrogen silicone oil and hexamethyldisiloxane to form low-hydrogen silicone oil, and propylene alcohol and a catalyst are added to a high-pressure reactor, and then the reaction mixture is evacuated, heated, and cooled to prepare the nano-additive;

[0023] Step 5: To ensure product quality and stability, a premixing process is required before preparation. The raw materials are mixed evenly according to the formula ratio. No impurities or contamination are allowed in the raw materials. The premixing time is 15-20 minutes, the speed is 1500r / min, and the premixing must be carried out in a sealed state.

[0024] Step 6: After the materials are evenly mixed, the materials are added to a screw extruder for extrusion molding, and then granulated by a granulator, wherein the operating temperature of the screw extruder is maintained at 170°C to 190°C;

[0025] Step 7: The particles prepared in step 6 are evenly fed into the grinding chamber of the grinding machine under the vibration of the vibrating feeder. After being ground, they are drawn into the cyclone separator by negative pressure in the pipeline. The air is discharged upward and the powder falls to the vibrating screen. The coarse powder on the screen continues to enter the grinding chamber for further grinding. The powder with appropriate fineness is put into the packaging bag as the product.

[0026] Beneficial effects of the present invention:

[0027] 1. The aging of asphalt causes a significant change in the content of the four components of asphalt, and there is a corresponding relationship between the proportion of the four components and the performance of asphalt. Therefore, the principle of traditional asphalt regeneration is to supplement the component loss caused by the aging process of asphalt, and then restore the performance of asphalt. However, the present invention "breaks" the strong charge attraction between the oxidized polar groups, so that the "colloid" structure formed by the polar groups of asphalt can be broken up or separated, thereby reducing the friction resistance of asphalt molecules, reducing viscosity, softening asphalt, and then restoring the performance of asphalt.

[0028] 2. Through the use of nano-scale rubber modified materials and composite nano-modified materials, the materials have excellent resistance to high-temperature deformation, fatigue resistance and self-healing (deformation recovery); through the use of nano-additives, the free density of small molecules in the material system is increased, effectively solving the problems of poor compatibility between old asphalt and regeneration agent, and poor diffusion and permeability between aged asphalt.

[0029] 3. Based on the diffusion characteristics of molecular structure: chain molecules, no or few polar groups, and small cohesive energy. Effectively enhance the interface performance, ensure the normal diffusion ability and normal construction performance of the regeneration agent. Make up for the shortcomings of existing materials. This nano-level regeneration agent has not been found in China. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0031] Figure 1 It is a schematic diagram of the comparison results of asphalt material test detection of the nano-scale asphalt regeneration and modification material and preparation method thereof of the present invention.

[0032] Figure 2 It is a schematic diagram for comparing asphalt material performance tests of the nano-scale asphalt regeneration and modification material and the preparation method thereof of the present invention. DETAILED DESCRIPTION

[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.

[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0036] Secondly, the present invention is described in detail with reference to the schematic diagram. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.

[0037] The following are examples of raw material sources and models are shown in the following table:

[0038]

[0039] Example 1

[0040] A nano-grade asphalt regeneration modification material is prepared from the following components by weight: 30 parts of composite nano-modified material, 25 parts of nano-grade fully vulcanized powder modified rubber, 10 parts of super tackifying resin, 15 parts of nano-auxiliary agent, and 20 parts of surfactant. It is prepared through factory prefabrication, catalytic reaction, premixing, extrusion granulation, and grinding processes.

[0041] The above-mentioned nano-scale asphalt regeneration modification material, wherein the composite nano-modified material is composed of nano-scale titanium dioxide or its modified polymer, UHMWPE (ultra-high molecular weight polyethylene) and calcium sulfate whiskers.

[0042] The above-mentioned nano-scale asphalt regeneration and modification material, wherein the super tackifying resin is preferably German KORESIN super tackifying resin.

[0043] The above-mentioned nano-scale asphalt regeneration modified material, wherein the nano-scale rubber modified material is preferably ultra-fine fully vulcanized powder rubber modified styrene-butadiene rubber.

[0044] In the above-mentioned nano-scale asphalt regeneration and modification material, the nano-additive is preferably a special modified polyether siloxane copolymer WET-511.

[0045] The above-mentioned nano-scale asphalt regeneration and modification material, wherein the surfactant material is preferably anhydrous sorbitan fatty acid ester. The preparation method of the above-mentioned nano-scale asphalt regeneration and modification material specifically comprises the following steps:

[0046] Step 1: Composite nano-modified material: Titanium butyl ester is used as raw material, hydrolyzed, polycondensed, and then polycondensed to obtain gel, and the gel is dried to prepare nano titanium dioxide; ultra-high molecular weight polyethylene is prepared by pressing, sintering, and pressing methods, and the process flow is as follows: prepare the raw materials in proportion; dry at 100°C and stir at high speed until the materials are evenly dispersed; press at 50Mpa, heat up to 170°C for sintering; press and shape again at 30Mpa, then cool to 70°C for demolding, polishing, and mechanical processing; calcium sulfate whiskers are obtained by mechanically stirring and mixing calcium salt and sulfate solutions, and aging for 24 hours. The three nano-material whiskers are prepared by a compound blending process in a ratio of 1:1:1.

[0047] Step 2: Super tackifying resin: It is synthesized through the condensation product of butylphenol and acetylene or prepared by processes such as decolorization, esterification, grafting, and stabilization with rosin and petroleum resin as basic raw materials.

[0048] Step 3: Ultrafine fully vulcanized powder modified rubber: using styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber, and chloroprene rubber as raw materials, cross-linking the latex through electron rays, and then spray drying to prepare it.

[0049] Step 4: The nano-additive is prepared from high-hydrogen silicone oil and hexamethyldisiloxane to form low-hydrogen silicone oil, and is added with propylene alcohol and a catalyst in a high-pressure reactor, and then evacuated, heated and cooled to prepare the nano-additive.

[0050] Step 5: To ensure product quality and stability, the premixing process is required before preparation. Mix all raw materials evenly according to the formula ratio, and no impurities or contamination is allowed in the raw materials. The premixing time is 15-20 minutes, and the speed is 1500r / min. The premixing must be carried out in a sealed state.

[0051] Step 6: After the materials are evenly mixed, add the materials into a screw extruder for extrusion molding, and then granulate them through a granulator, wherein the operating temperature of the screw extruder is maintained at 170°C to 190°C.

[0052] Step 7: The particles prepared in step 6 are evenly fed into the grinding chamber of the mill under the vibration of the vibrating feeder. After being ground, they are drawn to the cyclone separator by negative pressure in the pipeline. The air is discharged upward, and the powder falls to the vibrating screen. The coarse powder on the screen continues to enter the grinding chamber for re-grinding, and the powder with appropriate fineness is put into the packaging bag as the product. The main factors that the mill should pay attention to are the coarseness of the teeth, the running accuracy of the grinding disc, and the hardness of the grinding material.

[0053] Step 8: Add the nano-scale asphalt regeneration modified material prepared in step 7 to the aged base asphalt in an amount of 4% of the asphalt. According to the base asphalt production process, use a temperature control stirring device at 120°C and a speed of 3000r / min to stir for 15-30 minutes to make it evenly dispersed, and then the nano-scale regeneration asphalt material can be prepared.

[0054] The performance of the nano-scale regenerated asphalt material obtained in Example 1 was tested, and the specific test results are shown in Table 1.

[0055] Example 2

[0056] A nano-grade asphalt regeneration modification material is prepared from the following components by weight: 35 parts of composite nano-modified material, 35 parts of nano-grade fully vulcanized powder modified rubber, 5 parts of super tackifying resin, 5 parts of nano-additive, and 20 parts of surfactant. It is prepared through factory prefabrication, catalytic reaction, premixing, extrusion granulation, and grinding processes.

[0057] The above-mentioned nano-scale asphalt regeneration modification material, wherein the composite nano-modified material is composed of nano-scale titanium dioxide or its modified polymer, UHMWPE (ultra-high molecular weight polyethylene) and calcium sulfate whiskers.

[0058] The above-mentioned nano-scale asphalt regeneration and modification material, wherein the super tackifying resin is preferably German KORESIN super tackifying resin.

[0059] The above-mentioned nano-scale asphalt regeneration modified material, wherein the nano-scale rubber modified material is preferably ultra-fine fully vulcanized powder rubber modified styrene-butadiene rubber.

[0060] In the above-mentioned nano-scale asphalt regeneration and modification material, the nano-additive is preferably a special modified polyether siloxane copolymer WET-511.

[0061] The above-mentioned nano-scale asphalt regeneration and modification material, wherein the surfactant material is preferably anhydrous sorbitan fatty acid ester. The preparation method of the above-mentioned nano-scale asphalt regeneration and modification material specifically comprises the following steps:

[0062] Step 1: Composite nano-modified material: Titanium butyl ester is used as raw material, hydrolyzed, polycondensed, and then polycondensed to obtain gel, and the gel is dried to prepare nano titanium dioxide; ultra-high molecular weight polyethylene is prepared by pressing, sintering, and pressing methods, and the process flow is as follows: prepare the raw materials in proportion; dry at 100°C and stir at high speed until the materials are evenly dispersed; press at 50Mpa, heat up to 170°C for sintering; press and shape again at 30Mpa, then cool to 70°C for demolding, polishing, and mechanical processing; calcium sulfate whiskers are obtained by mechanically stirring and mixing calcium salt and sulfate solutions, and aging for 24 hours. The three nano-material whiskers are prepared by a compound blending process in a ratio of 1:1:1.

[0063] Step 2: Super tackifying resin: It is synthesized through the condensation product of butylphenol and acetylene or prepared by processes such as decolorization, esterification, grafting, and stabilization with rosin and petroleum resin as basic raw materials.

[0064] Step 3: Ultrafine fully vulcanized powder modified rubber: using styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber, and chloroprene rubber as raw materials, cross-linking the latex through electron rays, and then spray drying to prepare it.

[0065] Step 4: The nano-additive is prepared from high-hydrogen silicone oil and hexamethyldisiloxane to form low-hydrogen silicone oil, and is added with propylene alcohol and a catalyst in a high-pressure reactor, and then evacuated, heated and cooled to prepare the nano-additive.

[0066] Step 5: To ensure product quality and stability, the premixing process is required before preparation. Mix all raw materials evenly according to the formula ratio, and no impurities or contamination is allowed in the raw materials. The premixing time is 15-20 minutes, and the speed is 1500r / min. The premixing must be carried out in a sealed state.

[0067] Step 6: After the materials are evenly mixed, add the materials into a screw extruder for extrusion molding, and then granulate them through a granulator, wherein the operating temperature of the screw extruder is maintained at 170°C to 190°C.

[0068] Step 7: The particles prepared in step 6 are evenly fed into the grinding chamber of the mill under the vibration of the vibrating feeder. After being ground, they are drawn to the cyclone separator by negative pressure in the pipeline. The air is discharged upward, and the powder falls to the vibrating screen. The coarse powder on the screen continues to enter the grinding chamber for re-grinding, and the powder with appropriate fineness is put into the packaging bag as the product. The main factors that the mill should pay attention to are the coarseness of the teeth, the running accuracy of the grinding disc, and the hardness of the grinding material.

[0069] Step 8: Add the nano-scale asphalt regeneration modified material prepared in step 7 to the aged base asphalt in an amount of 4% of the asphalt. According to the base asphalt production process, use a temperature control stirring device at 120°C and a speed of 3000r / min to stir for 15-30 minutes to make it evenly dispersed, and then the nano-scale regeneration asphalt material can be prepared.

[0070] The performance of the nano-scale regenerated asphalt material obtained in Example 2 was tested, and the specific test results are shown in Table 2.

[0071] Example 3

[0072] A nano-grade asphalt regeneration modification material is prepared from the following components by weight: 35 parts of composite nano-modified material, 25 parts of nano-grade fully vulcanized powder modified rubber, 5 parts of super tackifying resin, 5 parts of nano-additive, and 30 parts of surfactant. It is prepared through factory prefabrication, catalytic reaction, premixing, extrusion granulation, and grinding processes.

[0073] The above-mentioned nano-scale asphalt regeneration modification material, wherein the composite nano-modified material is composed of nano-scale titanium dioxide or its modified polymer, UHMWPE (ultra-high molecular weight polyethylene) and calcium sulfate whiskers.

[0074] The above-mentioned nano-scale asphalt regeneration and modification material, wherein the super tackifying resin is preferably German KORESIN super tackifying resin.

[0075] The above-mentioned nano-scale asphalt regeneration modified material, wherein the nano-scale rubber modified material is preferably ultra-fine fully vulcanized powder rubber modified styrene-butadiene rubber.

[0076] In the above-mentioned nano-scale asphalt regeneration and modification material, the nano-additive is preferably a special modified polyether siloxane copolymer WET-511.

[0077] The above-mentioned nano-scale asphalt regeneration and modification material, wherein the surfactant material is preferably anhydrous sorbitan fatty acid ester. The preparation method of the above-mentioned nano-scale asphalt regeneration and modification material specifically comprises the following steps:

[0078] Step 1: Composite nano-modified material: Titanium butyl ester is used as raw material, hydrolyzed, polycondensed, and then polycondensed to obtain gel, and the gel is dried to prepare nano titanium dioxide; ultra-high molecular weight polyethylene is prepared by pressing, sintering, and pressing methods, and the process flow is as follows: prepare the raw materials in proportion; dry at 100°C and stir at high speed until the materials are evenly dispersed; press at 50Mpa, heat up to 170°C for sintering; press and shape again at 30Mpa, then cool to 70°C for demolding, polishing, and mechanical processing; calcium sulfate whiskers are obtained by mechanically stirring and mixing calcium salt and sulfate solutions, and aging for 24 hours. The three nano-material whiskers are prepared by a compound blending process in a ratio of 1:1:1.

[0079] Step 2: Super tackifying resin: It is synthesized through the condensation product of butylphenol and acetylene or prepared by processes such as decolorization, esterification, grafting, and stabilization with rosin and petroleum resin as basic raw materials.

[0080] Step 3: Ultrafine fully vulcanized powder modified rubber: using styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber, and chloroprene rubber as raw materials, cross-linking the latex through electron rays, and then spray drying to prepare it.

[0081] Step 4: The nano-additive is prepared from high-hydrogen silicone oil and hexamethyldisiloxane to form low-hydrogen silicone oil, and is added with propylene alcohol and a catalyst in a high-pressure reactor, and then evacuated, heated and cooled to prepare the nano-additive.

[0082] Step 5: To ensure product quality and stability, the premixing process is required before preparation. Mix all raw materials evenly according to the formula ratio, and no impurities or contamination is allowed in the raw materials. The premixing time is 15-20 minutes, and the speed is 1500r / min. The premixing must be carried out in a sealed state.

[0083] Step 6: After the materials are evenly mixed, add the materials into a screw extruder for extrusion molding, and then granulate them through a granulator, wherein the operating temperature of the screw extruder is maintained at 170°C to 190°C.

[0084] Step 7: The particles prepared in step 6 are evenly fed into the grinding chamber of the mill under the vibration of the vibrating feeder. After being ground, they are drawn to the cyclone separator by negative pressure in the pipeline. The air is discharged upward, and the powder falls to the vibrating screen. The coarse powder on the screen continues to enter the grinding chamber for re-grinding, and the powder with appropriate fineness is put into the packaging bag as the product. The main factors that the mill should pay attention to are the coarseness of the teeth, the running accuracy of the grinding disc, and the hardness of the grinding material.

[0085] Step 8: Add the nano-scale asphalt regeneration modified material prepared in step 7 to the aged base asphalt in an amount of 4% of the asphalt. According to the base asphalt production process, use a temperature control stirring device at 120°C and a speed of 3000r / min to stir for 15-30 minutes to make it evenly dispersed, and then the nano-scale regeneration asphalt material can be prepared.

[0086] The softening point (25°C), needle penetration (25°C, 5s, 100g), and elongation (10cm / min, 5°C) performance index comparison tests were carried out on the regenerated asphalt materials of Examples 1-3 and those using domestic regeneration agents and imported regeneration agents. The specific test results are shown in Table 1 (because this product is mainly benchmarked against foreign regeneration agents, the amount of regeneration agent added is 4% of the asphalt based on imported regeneration agents).

[0087] Table 1 Comparison results of asphalt material test

[0088]

[0089]

[0090] To further verify the effect, the performance comparison of Example 3 and the imported regeneration agent after adding them to the recycled asphalt mixture containing 50% asphalt recycled material is shown in Table 2.

[0091] Table 2 Comparison of the modification results of two regeneration agents on recycled asphalt mixture (the dosage is 0.4% of the mixture)

[0092]

[0093] Reference Figure 1 -2, the performance of recycled asphalt mixture was tested, and it was verified that the high temperature rutting resistance and low temperature cracking resistance of recycled asphalt mixture can fully meet the requirements of the specification, and achieve the performance of new asphalt mixture. The performance indicators of large-volume recycled materials are in line with the requirements of the specification and are better than imported regeneration agents.

[0094] The following conclusions can be drawn from the performance index comparison test between domestic and imported regeneration agents:

[0095] 1. Combining the three examples with the asphalt index test comparison of domestic regeneration agents and imported regeneration agents, it was found that the domestic regeneration agent had almost no regeneration effect when the addition amount was 4%;

[0096] 2. Imported regeneration agents have good regeneration and recovery effects. The patented nano-scale asphalt regeneration and modification material has obvious recovery effects, which is better than imported regeneration agents;

[0097] 3. The performance of recycled asphalt mixture was tested, and it was verified that the high-temperature rutting resistance and low-temperature cracking resistance of recycled asphalt mixture can fully meet the requirements of the specification and achieve the performance of new asphalt mixture. The performance indicators of large-volume recycled materials are in line with the requirements of the specification and are better than imported regeneration agents.

[0098] 4. The present invention develops a nano-scale asphalt regeneration and modification material. The quality of the regeneration agents on the market is uneven, and most of them have shortcomings such as poor anti-aging performance and poor diffusion and permeability with aged asphalt. The present invention uses nano-materials to effectively solve the problems of poor compatibility between old asphalt and regeneration agents, poor diffusion and permeability with aged asphalt, etc., effectively regulate and improve the component imbalance of asphalt materials caused by aging, restore the designed performance of the mixture, and thus repair the aged asphalt pavement.

[0099] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A nano-scale asphalt regeneration and modification material, characterized in that: It is prepared from the following components, by weight: 15-40 parts of composite nano-modified materials, 15-40 parts of nano-grade fully vulcanized powder modified rubber, 3-10 parts of super tackifying resin, 5-15 parts of nano-auxiliary agents, and 20-40 parts of surfactant materials. It is prepared through factory prefabrication, catalytic reaction, premixing, extrusion granulation, and grinding processes.

2. The nano-scale asphalt regeneration and modification material according to claim 1, characterized in that: The composite nano-modified material consists of nano-grade titanium dioxide or its modified polymer, UHMWPE (ultra-high molecular weight polyethylene) and calcium sulfate whiskers.

3. The nano-scale asphalt regeneration and modification material according to claim 2, characterized in that: The super tackifying resin is KORESIN super tackifying resin or GXH138 super tackifying resin.

4. The nano-scale asphalt regeneration and modification material according to claim 3 is characterized in that: The nano-scale rubber modified material is ultra-fine fully vulcanized powder rubber modified styrene-butadiene rubber.

5. The nano-scale asphalt regeneration and modification material according to claim 1, characterized in that: The nano auxiliary agent is a special modified polyether siloxane copolymer.

6. The nano-scale asphalt regeneration and modification material according to claim 5, characterized in that: The surface active material is fatty acid esters, including fatty acid glycerides and sorbitol fatty acid esters.

7. A method for preparing a nano-scale asphalt regeneration and modification material, characterized in that: The specific steps include: Step 1: Composite nano-modified material: using butyl titanate as raw material, hydrolyzing, polycondensing, and then polycondensing to obtain gel, and drying the gel to prepare nano titanium dioxide; ultra-high molecular weight polyethylene is prepared by pressing, sintering, and pressing methods, and the process flow is as follows: prepare the raw materials in proportion; dry at 100°C and stir at high speed until the materials are evenly dispersed; press at 50Mpa, heat up to 170°C for sintering; press and shape again at 30Mpa, then cool to 70°C for demolding, grinding, and mechanical processing to prepare; through calcium salt and sulfate solution, mechanical stirring, mixing, and then light stirring, aging for 24 hours to obtain calcium sulfate whiskers, and the three nano materials are prepared by compounding and blending in a ratio of 1:1:1; Step 2: Super tackifying resin: synthesized from the condensation product of butylphenol and acetylene or prepared from rosin and petroleum resin as basic raw materials through processes such as decolorization, esterification, grafting, and stabilization; Step 3: Nano-scale fully vulcanized powder modified rubber: using styrene-butadiene rubber (SBR), nitrile rubber (NBR), butadiene rubber, and chloroprene rubber as raw materials, cross-linking the latex through electron rays, and then spray drying to prepare it; Step 4: The nano-additive is prepared from high-hydrogen silicone oil and hexamethyldisiloxane to form low-hydrogen silicone oil, and propylene alcohol and a catalyst are added to a high-pressure reactor, and then the reaction mixture is evacuated, heated, and cooled to prepare the nano-additive; Step 5: To ensure product quality and stability, a premixing process is required before preparation. The raw materials are mixed evenly according to the formula ratio. No impurities or contamination are allowed in the raw materials. The premixing time is 15-20 minutes, the speed is 1500r / min, and the premixing must be carried out in a sealed state. Step 6: After the materials are evenly mixed, the materials are added to a screw extruder for extrusion molding, and then granulated by a granulator, wherein the operating temperature of the screw extruder is maintained at 170°C to 190°C; Step 7: The particles prepared in step 6 are evenly fed into the grinding chamber of the grinding machine under the vibration of the vibrating feeder. After being ground, they are drawn into the cyclone separator by negative pressure in the pipeline. The air is discharged upward and the powder falls to the vibrating screen. The coarse powder on the screen continues to enter the grinding chamber for further grinding. The powder with appropriate fineness is put into the packaging bag as the product.